2019
DOI: 10.3390/cancers11091328
|View full text |Cite
|
Sign up to set email alerts
|

Anthracyclines Suppress Both NADPH Oxidase- Dependent and -Independent NETosis in Human Neutrophils

Abstract: Neutrophil extracellular traps (NETs) are cytotoxic DNA-protein complexes that play positive and negative roles in combating infection, inflammation, organ damage, autoimmunity, sepsis and cancer. However, NETosis regulatory effects of most of the clinically used drugs are not clearly established. Several recent studies highlight the relevance of NETs in promoting both cancer cell death and metastasis. Here, we screened the NETosis regulatory ability of 126 compounds belonging to 39 classes of drugs commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…As a last resort in the anti-microbial defence strategy neutrophils undergo a programmed cell death known as NETosis, in order to (177)(178)(179)(180). Chromatin decondensation, a key part of NETosis, is mediated by protein arginine deiminase 4 (PAD-4), which citrullinates DNA, as well as myeloperoxidase and neutrophil elastase (181)(182)(183).…”
Section: Neutrophil Extracellular Trap Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a last resort in the anti-microbial defence strategy neutrophils undergo a programmed cell death known as NETosis, in order to (177)(178)(179)(180). Chromatin decondensation, a key part of NETosis, is mediated by protein arginine deiminase 4 (PAD-4), which citrullinates DNA, as well as myeloperoxidase and neutrophil elastase (181)(182)(183).…”
Section: Neutrophil Extracellular Trap Formationmentioning
confidence: 99%
“…As a last resort in the anti-microbial defence strategy neutrophils undergo a programmed cell death known as NETosis, in order to capture extracellular bacteria. The release of NETs, which are extruded DNA networks decorated with antimicrobial proteins and histones, can occur via ROS dependant or ROS independent pathways ( 177 180 ). Chromatin decondensation, a key part of NETosis, is mediated by protein arginine deiminase 4 (PAD-4), which citrullinates DNA, as well as myeloperoxidase and neutrophil elastase ( 181 183 ).…”
Section: Neutrophil Extracellular Trap Formationmentioning
confidence: 99%
“…Originally, it was reported that the presence of NADPH oxidase and myeloperoxidase (MPO) was necessary for the correct formation of NETs; until recently, all the activators capable of inducing NETs formation were known to require in some manner the presence of ROS ( 96 ). However, this has been a controversial theme in recent years due to the description of novel NETosis activation pathways that appear to be independent of NADPH oxidase ( 81 , 97 , 98 ).…”
Section: Reviewmentioning
confidence: 99%
“…The molecules of the anthracycline class intercalate between base pairs of DNA and RNA strands during DNA or RNA synthesis [90] and disrupt the activity of topoisomerase 2, which is essential for DNA replication [91]. It has been reported that anthracyclines can suppress NETosis through their intercalating activity, resulting in the alteration of the de-condensation process and thus in the abrogation of NET formation [92].…”
Section: Targeting Netosis To Prevent Metastasismentioning
confidence: 99%